[EMIM][Tf2N]-Modified silica as filler in mixed matrix membrane for carbon dioxide separation - Siti Nur Alwani, Shafie; Nik Abdul Hadi, Md Nordin; Muhammad Roil, Bilad; Nurasyikin, Misdan; Norazlianie, Sazali; Zulfan Adi, Putra; Mohd Dzul Hakim, Wirzal; Alamin, Idris; Juhana, Jaafar; Zakaria, Man (MDPI, 2021)
: This study focuses on the effect of modified silica fillers by [EMIN][Tf2N] via physical adsorption on the CO2 separation performance of a mixed matrix membrane (MMM). The ILmodified silica was successfully synthesized as the presence of fluorine element was observed in both Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectrometer (XPS) analyses. The prepared MMMs with different loadings of the IL-modified silica were then compared with an unmodified silica counterpart and neat membrane. The morphology of IL-modified MMMs was observed to have insignificant changes, while polymer chains of were found to be slightly more flexible compared to their counterpart. At 2 bar of operating pressure, a significant increase in performance was observed with the incorporation of 3 wt% Sil-IL fillers compared to that of pure polycarbonate (PC). The permeability increased from 353 to 1151 Barrer while the CO2/CH4 selectivity increased from 20 to 76. The aforementioned increment also exceeded the Robeson upper bound. This indicates that the incorporation of fillers surface-modified with ionic liquid in an organic membrane is worth exploring for CO2 separation